Debt management in Brazil : evaluation of the real plan and challenges ahead - Bevilaqua, Afonso S. (Policy research working paper, 2000)
In 1994-98, Brazil's domestic debt grew very rapidly while remaining short in maturity. The main policy recommendations for managing this domestic debt situation: maintain a tighter fiscal stance and consider the use of inflation-linked bonds